Mark - Hurtado, Larry (Grand Rapids : Baker Publishing Group, 2011)
A section-by-section commentary on the New Testament, written by scholars for pastors, teachers, and students of the Bible.
Reference AidsBooks on Mark; Subject Index; Scripture Index; Old Testament; New Testament; Apocrypha; Pseudepigrapha; Josephus; Church Fathers; Other Early Writings.
Description based upon print version of record.
Keywords: Bible. -- Commentaries; Bible; Religion; Electronic books